Penerapan Metode Hafalan yang Asik 3M (Menyimak, Mengulang, Murja’ah) - Erni Asneli; Cellyna Setyowati (Yayasan Literasi Sains Indonesia, 2022)
As students, we act as agents of change where we must be able to actualize ourselves. One of the forms is by conducting this Field Work Practice. In this case, it is expected to be able to implement and master the theories that have been obtained. Memorizing is an activity by embedding a verbal material in his memory, so that later it can be recalled according to the original material. However, not all children are easy in the memorization process, because children's memory is different. The limited memory of children is very influential in the way a child memorizes. The same thing happened to one of the children at the Al-Jami'yatul Washliyah Orphanage who needed a solution to a problem related to memorization. The process of providing assistance was also carried out in the PKL I mini project activity, using the case work method through the general and general intervention stages. This stage consists of engagement, intake, contract, assessment, planning, intervention, evaluation, and termination. The focus in solving client problems is to use the cool memorization method, namely 3M (Listening, Repeating, Murja'ah) as a strategy designed together to facilitate the memorization process and increase the client's confidence. The purpose of this program was successfully implemented. This can be seen from the development of clients who are already fluent in memorizing surahs and returning to their social functioning in the orphanage environment.